Isu Dan Tantangan Kompetensi Dewan Pengawas Syariah Di Indonesia - Nadia Farhana Izzatika; Ahmad Tarmidzi Lubis (Jurnal Akuntansi dan Keuangan Islam, 2016)
This study aims to discover and know the issues and challenges the competence of the shariah supervisory board in Indonesia. Given the inequality between sharia accounting competence. The discussion of this study will combine engineering library research with interviews with practitioners and academics who work in auditing sharia. The results of this study discovered that there are three issues related to the competence of shariah supervisory board in Indonesia, which is, 1) Unbalance the competency of the shariah supervisory board in accounting and finance with competence in the field of sharia, 2) Certification shariah supervisory board in Indonesia has not been optimal, 3) Still lack a college that provides programs of study sharia accounting so that the shariah supervisory board there is still limited. Referring to the issue of the things that are a challenge related to the competence of auditors of sharia in Indonesia, which is, In terms of the challenges of 1) Upgrading the competence of the shariah supervisory board, 2) Cooperation between DSN-MUI with the FSA in creating shariah supervisory board certification, 3) Educational institutions are able to meet the needs of related industries shariah supervisory board.